Modification of the Ceramic Implant Surfaces from Zirconia by the Magnetron Sputtering of Different Calcium Phosphate Targets: A Comparative Study - Kozelskaya A. I. Anna Ivanovna; Bolbasov E. N. Evgeny Nikolaevich; Golovkin A. S. Aleksey Sergeevich; Mishanin A. I. Aleksandr; Viknyanshchuk A. N. Alisa; Shesterikov E. V. Evgeny Viktorovich; Ashrafov A. Kh. Andrey Khakimovich; Novikov V. A. Vadim Aleksandrovich; Fedotkin A. Yu. Aleksandr Yurjevich; Khlusov I. A. Igor Albertovich; Tverdokhlebov S. I. Sergei Ivanovich (2018, 2018)
Title screen